How do you solve 4x+y=−9 and 3x+7y=37?
Answers
Answered by
11
Given equations,
4x + y = - 9 ...... (i)
3x + 7y = 37 ..... (ii)
By using Elimination method,
Multiplying equation (i) by 7,
7(4x + y = - 9)
28x + 7y = - 63 ..... (iii)
Subtracting equation (iii) from equation (ii),
![28x \: + 7y \: = - 9 \\ 3x \: + \: 7y \: = \: 37 28x \: + 7y \: = - 9 \\ 3x \: + \: 7y \: = \: 37](https://tex.z-dn.net/?f=28x+%5C%3A+%2B+7y+%5C%3A+%3D+-+9+%5C%5C+3x+%5C%3A+%2B+%5C%3A+7y+%5C%3A+%3D+%5C%3A+37+)
By subtracting we obtain,
=> 24x = 28
=> x =
=> x =
=> x =
=> x =
=> x =
Substituting x =
in equation (i),
4x + y = - 9
14 + 3y = - 3
3y = - 3 - 14
3y = - 17
y =
4x + y = - 9 ...... (i)
3x + 7y = 37 ..... (ii)
By using Elimination method,
Multiplying equation (i) by 7,
7(4x + y = - 9)
28x + 7y = - 63 ..... (iii)
Subtracting equation (iii) from equation (ii),
By subtracting we obtain,
=> 24x = 28
=> x =
=> x =
=> x =
=> x =
=> x =
Substituting x =
4x + y = - 9
14 + 3y = - 3
3y = - 3 - 14
3y = - 17
y =
LovelyG:
There's a mistake, kindly fix it!
Answered by
0
Answer:
x = - 4, y = 7
Step-by-step explanation:
4x + y = - 9...... (i)
3x + 7y = 37.......(ii)
We will solve this question, using elimination and substitution method;
Multiplying eqⁿ (i) by 7, we get ;
4x + y = - 9
⇒ 7 (4x + y) = 7 * (-9)
⇒ 28x + 7y = - 63...... (iii)
Subtracting eqⁿ (ii) from (iii), we get;
![28x + 7y = - 63 \\ \: 3x \: + \: 7y = \: \: \ 37 \\ - \: \: \: \: \: \: \: \: - \: \: \: \: \: \: \: - 28x + 7y = - 63 \\ \: 3x \: + \: 7y = \: \: \ 37 \\ - \: \: \: \: \: \: \: \: - \: \: \: \: \: \: \: -](https://tex.z-dn.net/?f=28x+%2B+7y+%3D+-+63+%5C%5C+%5C%3A+3x+%5C%3A+%2B+%5C%3A+7y+%3D+%5C%3A+%5C%3A+%5C+37+%5C%5C+-+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+-+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+-+)
________________
![25x = - 100 \\ \\ x = \frac{ - 100}{25} \\ \\ \boxed{ \bf x = - 4} 25x = - 100 \\ \\ x = \frac{ - 100}{25} \\ \\ \boxed{ \bf x = - 4}](https://tex.z-dn.net/?f=25x+%3D+-+100+%5C%5C+%5C%5C+x+%3D+%5Cfrac%7B+-+100%7D%7B25%7D+%5C%5C+%5C%5C+%5Cboxed%7B+%5Cbf+x+%3D+-+4%7D)
Substituting the value of x in (i),
4x + y = - 9
⇒ 4 (-4) + y = - 9
⇒ - 16 + y = - 9
⇒ y = - 9 + 16
![\boxed{\bf \implies y = 7} \boxed{\bf \implies y = 7}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cbf+%5Cimplies+y+%3D+7%7D)
Hence, the value of x is - 4 and y is 7.
x = - 4, y = 7
Step-by-step explanation:
4x + y = - 9...... (i)
3x + 7y = 37.......(ii)
We will solve this question, using elimination and substitution method;
Multiplying eqⁿ (i) by 7, we get ;
4x + y = - 9
⇒ 7 (4x + y) = 7 * (-9)
⇒ 28x + 7y = - 63...... (iii)
Subtracting eqⁿ (ii) from (iii), we get;
________________
Substituting the value of x in (i),
4x + y = - 9
⇒ 4 (-4) + y = - 9
⇒ - 16 + y = - 9
⇒ y = - 9 + 16
Hence, the value of x is - 4 and y is 7.
Similar questions